2021
DOI: 10.1002/cpp.2582
|View full text |Cite
|
Sign up to set email alerts
|

The effect of childhood maltreatment on suicidal ideation through cognitive emotion regulation strategies and specific obsessive–compulsive symptoms in obsessive–compulsive disorder

Abstract: Childhood maltreatment is thought to be associated with suicidality in patients with obsessive-compulsive disorder (OCD). Although the underlying mechanism of this relationship is not clear, cognitive emotion regulation strategies (CERSs) and the specific OC symptoms including unacceptable obsessional thoughts (UOTs) and responsibility for harm (RFH) may underlie this link. Accordingly, the study aimed to assess the effect of childhood maltreatment on suicidal ideation through UOTs, RFH and adaptive and malada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…The present study aimed to evaluate the effects of OC symptom dimensions and OCD symptom severity on suicidal ideation through the role of specific stress responses to COVID‐19 in a clinical group of patients with OCD. The prevalence of suicide attempts in patients was 22.7%, consistent with rates reported in the previous studies (i.e., 1 to 52%; Albert et al, 2019; De La Vega et al, 2018; Dell'Osso et al, 2018; Kim et al, 2016; Rajabi Khamesi et al, in press; Pellegrini et al, 2020). Discrepancies in reporting the prevalence of suicide attempts in these studies may be due to the study samples differing in the prevalence of comorbid psychiatric disorders, especially BD, MDD, and SUDs (Albert et al, 2018) as well as heterogeneity regarding age ranges, sample size, study design, gender distribution, and various tools assessing suicide attempts (see Angelakis et al, 2015; Pellegrini et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present study aimed to evaluate the effects of OC symptom dimensions and OCD symptom severity on suicidal ideation through the role of specific stress responses to COVID‐19 in a clinical group of patients with OCD. The prevalence of suicide attempts in patients was 22.7%, consistent with rates reported in the previous studies (i.e., 1 to 52%; Albert et al, 2019; De La Vega et al, 2018; Dell'Osso et al, 2018; Kim et al, 2016; Rajabi Khamesi et al, in press; Pellegrini et al, 2020). Discrepancies in reporting the prevalence of suicide attempts in these studies may be due to the study samples differing in the prevalence of comorbid psychiatric disorders, especially BD, MDD, and SUDs (Albert et al, 2018) as well as heterogeneity regarding age ranges, sample size, study design, gender distribution, and various tools assessing suicide attempts (see Angelakis et al, 2015; Pellegrini et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…The results of the current study showed that, among the OC symptom dimensions, responsibility for harm and unacceptable obsessional thoughts as well as OCD severity indirectly affected suicidal ideation through stress responses in reaction to the pandemic, specifically traumatic stress symptoms and compulsive checking, after controlling for covariates of general depression and anxiety, comorbidity, and lifetime suicide attempts. These results are consistent with prior findings showing the significant role of these same OC symptom dimensions and OCD severity in suicidality, including suicidal ideation (e.g., Albert et al, 2019; Balci & Sevincok, 2010; De Berardis et al, 2015; DeVylder et al, 2012; Khosravani, Bastan, et al, 2017; Khosravani, Kamali, et al, 2017; Kim et al, 2016; Krebs et al, 2020; Rajabi Khamesi et al, in press; Torres et al, 2011; Velloso et al, 2016). Further, the present findings are consistent with the results of previous studies reporting the relationships between COVID‐19 and suicidal ideation in patients with OCD (Benatti, Albert, et al, 2020).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Experiencing traumatic events during childhood when the individual is psychologically and neurodevelopmentally vulnerable is associated with an increased risk of developing psychopathology and SI later in life. 60 , 61 Especially childhood sexual abuse and the development of early maladaptive schemas. 6 , 62 As previously mentioned, childhood abuse been suggested to be the most notable variable distinguishing SI from SA in OCD.…”
Section: Methodsmentioning
confidence: 99%
“… 65 However, in individuals with OCD and a history of childhood maltreatment, unacceptable obsessional thoughts and responsibility for harm may be critical to this connection. 61 Emotion regulation has also been proposed as a potential underlying mechanism of OCD-related suicidality, due to a critical disruption of these abilities following an adverse event. 61 , 66 …”
Section: Methodsmentioning
confidence: 99%